Diverse motif ensembles specify non-redundant DNA binding activities of AP-1 family members in macrophages - Gregory J. Fonseca (Nature Portfolio, 2019)
Transcription factors of the AP-1 family can play diverse roles despite recognizing the same DNA sequence. Here the authors investigate the DNA binding activities of AP-1 members in mouse macrophages and apply a machine learning approach to identify motifs predicted to drive factor-specific binding profiles.